2020
DOI: 10.1108/lhtn-11-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

To frame or not to frame: creating a metaliteracy course for online Ed.D. students

Melissa D. Atkinson

Abstract: Purpose The purpose of this study is to create a course in a learning management system (LMS), Canvas, for online Ed.D. students and determine if the course can improve scores measuring metaliteracy concepts from pretest to posttest. The course assessed knowledge of metaliteracy goals and objectives instead of using the ACRL Framework. This paper reports on the creation of the course, results of the pretest-posttest, a mapping of metaliteracy goals and objectives with the ACRL Framework and recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Though until recently; they have been exposed very little Pre and post assessment study critical examination, these models have widespread acceptance among librarians and other educators (McNicol et al, 2014). Still, recent research showed preferences in ACRL framework for adopting in the higher education for a more scaffolded and embedded approach for the university (Albert et al, 2020;Atkinson, 2020;Davidson Squibb and Zanzucchi, 2020;Fite and Jackson, 2018;Gainey et al, 2019;Gunasekara and Gerts, 2017;Lehner-Quam and Pitts, 2019;Sample, 2020;Schwartz, 2018;Sharun, 2019). Most of the researchers stressed the necessity of IL and required research skills in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though until recently; they have been exposed very little Pre and post assessment study critical examination, these models have widespread acceptance among librarians and other educators (McNicol et al, 2014). Still, recent research showed preferences in ACRL framework for adopting in the higher education for a more scaffolded and embedded approach for the university (Albert et al, 2020;Atkinson, 2020;Davidson Squibb and Zanzucchi, 2020;Fite and Jackson, 2018;Gainey et al, 2019;Gunasekara and Gerts, 2017;Lehner-Quam and Pitts, 2019;Sample, 2020;Schwartz, 2018;Sharun, 2019). Most of the researchers stressed the necessity of IL and required research skills in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model also informed the design of three prior MOOCs in the connectivist and xMOOC formats (O'Brien et al, 2017) as well as a competency-based digital badging system (O'Brien, 2018). Further, the metaliteracy goals and learning objectives were analyzed as part of a study that examined a non-credit online course designed for doctoral students (Atkinson, 2020).…”
Section: Metaliteracymentioning
confidence: 99%